2015
DOI: 10.1007/s00251-015-0838-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the salmonid IL-17A/F1a/b, IL-17A/F2b, IL-17A/F3 and IL-17N genes and analysis of their expression following in vitro stimulation and infection

Abstract: This study identifies four new IL-17A/F isoforms in salmonids, as well as IL-17N. IL-17A/F1 and IL-17A/F2 are each represented by two paralogues, with a predicted pseudogene of IL-17N also apparent in the salmonid genome. Analysis of the sequences and genes of the known IL-17A/F and IL-17N molecules suggests that IL-17N is a member within the IL-17A/F subfamily. Analysis of factors that modulated the expression of these genes showed that PHA and PMA were good inducers of salmon IL-17A/F1a and IL-17A/F2a, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 55 publications
2
48
0
Order By: Relevance
“…Thus, spleen leukocytes from control and infected fish were isolated 4 dpi and sorted into four lymphocyte populations, CD4 DP, CD4-2 SP, CD8α + , and CD4-1 − /CD4-2 − /CD8α − lymphocytes (Neg). In line with previous reports (29, 46), whole spleen leukocytes (WSLs) in infected fish showed higher expression levels of il-2 , il-10 , ifng , il-17a/f-1a , il-21b , and il-22 cytokines when compared to those in control fish, whereas the expression levels of il-4/13a and il-21a remained unchanged (Fig. 5).…”
Section: Resultssupporting
confidence: 92%
“…Thus, spleen leukocytes from control and infected fish were isolated 4 dpi and sorted into four lymphocyte populations, CD4 DP, CD4-2 SP, CD8α + , and CD4-1 − /CD4-2 − /CD8α − lymphocytes (Neg). In line with previous reports (29, 46), whole spleen leukocytes (WSLs) in infected fish showed higher expression levels of il-2 , il-10 , ifng , il-17a/f-1a , il-21b , and il-22 cytokines when compared to those in control fish, whereas the expression levels of il-4/13a and il-21a remained unchanged (Fig. 5).…”
Section: Resultssupporting
confidence: 92%
“…Purified Atlantic salmon GALT leucocytes obtained using protocol-3, were suspended in RPMI-1640 containing P/S and 10% FBS, then plated at 2x10 6 cells /well into 12 well plates and cultured at 20 o C. The cells, from individual fish, were then stimulated with 10 μg /ml phytohaemagglutinin from Phaseolus vulgaris (PHA, Sigma), 50 μg /ml LPS, 100 μg /ml polyinosinic acid: polycytidylic acid (poly I:C, Sigma), 100 ng /ml recombinant flagellin from Yersinia ruckeri (rYRF, [26], 25 ng /ml IL-1β1 [27], 100 ng /ml IL-2B [28], 100 ng /ml IL-6 [29], 200 ng /ml IL-21 [30] and 20 ng /ml IFN-α2/IFN2 [31]. All doses used were previously shown to be optimal for trout and Atlantic salmon cells [32,33,34], and the cytokine paralogues chosen have known bioactivity on leucocytes from other tissues. Untreated cells were included as controls.…”
Section: Atlantic Salmon Galt Leucocyte Analysismentioning
confidence: 99%
“…It has been reported that expression levels of IL-17A/F1, 2, and 3 genes fluctuate at the mRNA level during bacterial infection in multiple fish species. Yersinia ruckeri upregulates salmonid IL-17A/F1, 2, and 3 in the spleen (22), whereas Aeromonas hydrophila up-regulates large yellow croaker counterparts in the head, kidney, and gill (23). However, details regarding the mechanism of fish IL-17A/F gene regulation of the intestinal tract microbiome are unknown.…”
Section: Introductionmentioning
confidence: 99%